Answer:
<h2> The cost of a candy is $1.25</h2>
Step-by-step explanation:
given the total amount at hand is $25
let the price of candy be x
then the cost of 3 candy will be 3x
the cost of a candy snake is $12.50.
balance at hand after the end of buying $8.75
the total expenses summed up must equal the initial amount at hand which is $25
the expression for the scenario is 3x+12.5+8.75=25
3x+21.25=25
3x=25-21.25
3x=3.75
x=3.75/3
x=$1.25
The cost of a candy is $1.25
Answer:
<em>(a). P(x) = 8x - 112,000 </em>
<em> (b). $80,000 </em>
Step-by-step explanation:
(a). P(x) = R(x) - C(x)
P(x) = 50x - 112,000 - 42x
<em>P(x) = 8x - 112,000</em>
(b). P(24,000) = 8(24,000) - 112,000 = <em>80,000</em>
----------------------------------------
(a). <em>P(x) = 8x - 112,000</em>
Answer:
first one should be $35.52
Second one $18.60
Step-by-step explanation:
Answer:
<h2>112°</h2>
Step-by-step explanation:
Angle 8 will also be 112° because both of them( Angle 2 and Angle 8) are exterior alternate angles and exterior alternate angles are always equal.
So Angle 8 = 112°